Characteristics of Presbycusis Patients at RSUD Prof. Dr. Margono Soekarjo Purwokerto - Mukhammad Ilham Abdurrohman; Wahyu Dwi Kusdaryanto; Ary Nahdiyani Amalia; Anton Budi Darmawan; Rani Afifah Nur Hestiyani (Medical and Health Journal, 2026)
Presbycusis is a progressive sensorineural hearing loss commonly affecting the elderly and significantly reducing quality of life. RSUD Prof. Dr. Margono Soekarjo Purwokerto, as a referral hospital, treats a large number of elderly patients, making characterization of presbycusis patients essential. This study aimed to describe the characteristics of presbycusis patients based on age, sex, occupation, comorbidities, and degree of hearing loss. A descriptive quantitative study with a retrospective approach was conducted using total sampling of presbycusis patients at the ENT outpatient clinic from 2022 to 2024. A total of 81 patients met the inclusion criteria. Most patients were male and aged 61–74 years. The most common occupation was farmer, and hypertension was the most frequent comorbidity. Hearing loss was generally bilateral with moderate to moderately severe degree.